The effect of lateral decubitus position on intraocular pressure in healthy young subjects - Lee, Jong Yeon; Yoo, Chungkwon; Jung, Jae Hoon; Hwang, Young Hoon; Kim, Yong Yeon (Acta ophthalmologica (Oxford, England), 2012)
. Purpose:  To investigate the effect of change of body posture from supine to lateral decubitus position (LDP) on intraocular pressure (IOP) in healthy young subjects. Methods:  We evaluated 38 eyes of 19 healthy young Korean subjects. IOP was measured using Tonopen XL® in both eyes in the sitting and supine position, 5 and 30 min after right LDP and 5 min after returning to the supine position. A week later, IOP was measured in the same sequence except that the subjects assumed the left LDP. The eye on the lower side in the LDP was termed as a dependent eye. Results:  The mean IOP of the dependent eyes increased significantly at 5 min after changing from supine to right (16.26 ± 2.73 mmHg versus 18.54 ± 2.95 mmHg, p < 0.01) or left LDP (15.53 ± 2.41 mmHg versus 17.53 ± 3.37 mmHg, p < 0.01); this IOP increase in the dependent eyes persisted at 30 min after changing to right (18.47 ± 2.97 mmHg, p < 0.01) or left LDP (17.79 ± 2.20 mmHg, p < 0.01). Upon returning to the supine position, IOP of the dependent eyes decreased significantly (16.83 ± 2.67 mmHg, p < 0.01 for right LDP and 16.47 ± 2.32 mmHg, p < 0.01 for left). However, this effect of the positional change was not found in the non‐dependent eyes (all, p > 0.05). Mean IOP in the dependent eye was significantly higher than that in the non‐dependent eye at 30 min after changing to the right (+0.89 ± 1.52 mmHg) or left LDP (+1.84 ± 2.03 mmHg). Conclusion:  The postural change from supine to LDP significantly increased IOP of the dependent eyes.